Closed‐form solutions of coherent anti‐Stokes Raman signals generated by means of time asymmetric probe pulses. (8th June 2015) - Marrocco, M.; Joubert, Pierre; Lavorel, Bruno; Kiefer, Johannes; Moger, Julian
<x xml:space="preserve">Abstract</x> Under impulsive excitation of vibrational and rotational levels, coherent anti‐Stokes Raman scattering (CARS) is strongly dependent on the shape of the probe laser pulses. Here, we investigate this dependence for picosecond probe durations by showing for the first time that closed‐form solutions are achievable not only for fundamental probe pulses (Gaussian and hyperbolic secant) but also for their time asymmetric versions that better simulate some realistic experimental conditions. Thanks to this achievement, CARS lineshapes and time decays of Raman resonances can be studied without the numerical efforts that are common in the conventional approach to time‐resolved CARS. Copyright © 2015 John Wiley & Sons, Ltd.